Стратиграфические исследования на юго-восточном склоне мыса Тешкли-бурун (Мангуп) - Герцен, А.Г.; Землякова, А.Ю.; Науменко, В.Е.; Смокотина, А.В. (Материалы по археологии, истории и этнографии Таврии, 2006)
Мангупское городище, расположенное на одноименном изолированном плато с высшей точкой около 600 м над уровнем моря, представляет собой уникальный пример сосредоточения на одном памятнике разновременных и разноплановых объектов III-XVIII вв. Их многолетнее археологическое изучение позволяет наметить в общих чертах основные этапы истории городища. The results of stratigraphic research on the south-eastern slope of Teshkly- Burun cape containing important information on the main periods of functioning of the settlement in this part of Mangup plateau are published in this article. Cultural horizons fixed within the excavation area are interpreted as a single discharge of accumulated debris strata from the surface of the cape to its slopes as a result of building activities on the acropolis of Mangup site.